Coercion and choice in parent–child live kidney donation. Issue 4 (6th November 2014) - Burnell, Philippa; Hulton, Sally-Anne; Draper, Heather
Abstract : This paper explores whether donor-parents felt coerced to donate a kidney to their child. There is a paucity of UK literature on parental live kidney donors and the voluntariness of their decision-making. Data were gathered as part of a study exploring parental experiences of consenting for live donation at a UK specialist children's hospital. Parents who donated a kidney to their child between September 2006 and December 2010 and who consented at their child's hospital to be referred to an adult unit for consideration for live donation were invited to participate. Of the 19 eligible parents, seven fathers and three mothers consented to be interviewed. Their primary motivation for donation was being a parent (more specifically, the parent of a sick child). Participants expressed this in terms of parental love and concern. Participants conveyed certainty about their decision and viewed live donation as a positive opportunity. Most participants regarded the decision to donate, or not donate, as one every parent is entitled to make for their own reasons. In discussing our findings, we argue that when parents do not separate their child's interests from their own, this does not necessarily compromise autonomous decision-making: using one's own moral values to constrain one's own choices can be compatible with voluntary decision-making. Indeed, choices may be more constrained when parents are unable to donate, because this reduces the options available to parents to help their child.